The Role of Diasporas in the Current World Politics - I. D. Loshkariov (Vestnik MGIMO-Universiteta)
The author's intention is to access the impact that diasporas have on world politics. The notion “diaspora” implies a transnational migrant community, which maintains material and emotional bonds with territory of origin and simultaneously adapts to limitations and possibilities of host society. The emotional component of a community entails psychosocial complex that includes the group solidarity and certain myths about the territory of origin. Taking into account the specifics of a given community, diasporas meet in general all the requirements of a non-state actor that have been elaborated in the current studies on the world politics. In particular, a diasporas exist independently and participates in the transnational interactions. Moreover, there are several situations which enhance diaspora’s ability to interfere. These situations may include the unsatisfactory status of the given community, migrants’ desire to improve certain political or economic conditions in the territory of origin, the prerequisites for changes in the relationships between the hostland and the homeland, urgent crises in the country of origin. In addition, diasporal influence depends on demographic and geographic characteristics of the particular community. Diasporas achieve their goals on global, regional and national levels mainly by influencing state’s institutions. However, some developments have been evolved that can facilitate a substantive diasporas’ involvement in the world political processes, involvement without dependence on state’s capabilities. Elite of the community plays a crucial role in the resource management. The elite presents “the controlling centre” that forges a strategy of action and makes transactions of resources. Stability within “the controlling centre” can be named as an indicator of diaspora’s ability to manage the potential available.